High level of deoxycholic acid in human bile does not promote cholesterol gallstone formation - Gustafsson, Ulf (World J Gastroenterol, 2003)
AIM: To study whether patients with excess deoxycholic acid (DCA) differ from those with normal percentage of DCA with respect to biliary lipid composition and cholesterol saturation of gallbladder bile. METHODS: Bile was collected during operation through puncturing into the gallbladder from 122 cholesterol gallstone patients and 46 gallstone-free subjects undergoing cholecystectomy. Clinical data, biliary lipids, bile acid composition, presence of crystals and nucleation time were analyzed. RESULTS: A subgroup of gallstone patients displayed a higher proportion of DCA in bile than gallstone free subjects. By choosing a cut-off level of the 90th percentile, a group of 13 gallstone patients with high DCA levels (mean 50 percent of total bile acids) and a large group of 109 patients with normal DCA levels (mean 21 percent of total bile acids) were obtained. The mean age of the patients with high DCA levels was higher than that of the group with normal levels (mean age: 62 years vs 45 years) and so was the mean BMI (28.3 vs 24.7). Plasma levels of cholesterol and triglycerides were slightly higher in the DCA excess groups compared with those in the normal DCA group. There was no difference in biliary lipid composition, cholesterol saturation, nucleation time or occurrence of cholesterol crystals in bile between patients with high and normal levels of DCA. CONCLUSION: Gallstone patients with excess DCA were of older age and had higher BMI than patients with normal DCA. The two groups of patients did not differ with respect to biliary lipid composition, cholesterol saturation, nucleation time or occurrence of cholesterol crystals. It is concluded that DCA in bile does not seem to contribute to gallstone formation in cholesterol gallstone patients.